Identification of outstanding faba bean populations collected in the State of Mexico - Orozco Colin, Neri; Pérez López, Delfina de Jesús; González Huerta, Andrés; Franco Mora, Omar; Gutiérrez Rodríguez, Francisco; Rubí Arriaga, Martin; Castañeda Vildózola, Álvaro; Balbuena Melgarejo, Artemio (Revista Mexicana de Ciencias Agrícolas, 2018)
For the largest bean consumption in low-income sectors in Mexico and lack of availability of commercial varieties; this study was conducted in 2011 in San Mateo Otzacatipan, San Nicolás Guadalupe and Metepec, to evaluate 12 agronomic traits in 36 populations of faba bean (Vicia faba L.) collected in the State of Mexico, in order to select populations with outstanding phenotypic characteristics. The experimental design was randomized complete block with three replications. The data analysis through the locations was done as a series of experiments in space. The experimental plot consisted of three rows of 4 m length and 0.80 m width. Significant differences were detected between populations (G), among environments (A) and G x A interaction in 11 variables. In SNG were recorded the highest average in seed weight and yield components; populations 36, 1, 5 and 7 were the most outstanding. These four populations could be used in a breeding program or technology generation.
Keywords: Vicia faba; combined analysis of variance; genotypes; yield components; yield